Answer:
Infinite Solution
Step-by-step explanation:
Given :
-----(A)
------(B)
To Find : Solution of the given system of equations
Solution :
We will solve it by using substitution method
Finding the value of x from equation (B)
⇒
⇒
⇒![x= \frac{-30+9y}{-9}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B-30%2B9y%7D%7B-9%7D)
⇒![x= \frac{-10+3y}{-3}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B-10%2B3y%7D%7B-3%7D)
Putting this value of x in equation (B)
⇒ ![3( \frac{-10+3y}{-3})+3y=10](https://tex.z-dn.net/?f=3%28%20%5Cfrac%7B-10%2B3y%7D%7B-3%7D%29%2B3y%3D10)
⇒![10-3y+3y = 10](https://tex.z-dn.net/?f=10-3y%2B3y%20%3D%2010)
⇒![10= 10](https://tex.z-dn.net/?f=10%3D%2010)
Since x and y both gets eliminated from the equation we got 10 = 10
Since the equations represent the same line.
If a consistent dependent system that has an infinite number of solutions
Hence there is infinite solution .